The Rough Guide to Conspiracy Theories - McConnachie, James and Tudge, Robin (London Rough Guides, 2008)
Everything you think you know is a lie. Or is it? The Rough Guide to Conspiracy Theories is the definitive guide to the world"s most controversial theories. With updated information on all the most infamous conspiracies, from phony crucifixions to who really did kill JFK, this fully up-dated guide also covers the murders of Alexander Litvinenko and Benasir Bhutto, the London bombings and the Iraq War, as well as the inquest into Princess Diana's death. The guide is a thoroughly researched exploration into this compulsive and, at times, amusing phenomenon, with fascinating discourse and a keen sense of the satirical. For both the believers and the cynics, The Rough Guide to Conspiracy Theories sorts the myths from the realities.
Include Illustrations and Index
Keywords: Conspiracies